Hot dip galvanized steel sheet

By adjusting the chemical composition and coating structure of the hot-dip galvanized steel plate, the welding problem caused by gaps in the zinc plating layer of the hot-stamped molded body is solved, and excellent spot weldability and the strength required for the hot-stamped molded body are achieved.

CN116137870BActive Publication Date: 2025-02-18NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180063358.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-12
Filing Date
2021-07-20
Publication Date
2025-02-18
Estimated Expiration
2041-07-20

AI Technical Summary

Technical Problem

During the spot welding process, there are gaps in the zinc-based plating layer of the hot stamped molded body, resulting in poor welding or the need to stop manufacturing lines and replace the copper electrode, affecting the process efficiency.

Method used

By adjusting the chemical composition and coating structure of the hot-dip galvanized steel plate, specific measures include setting the average crystal particle size exceeding 4.0 μm in the depth area of ​​the steel plate surface, and adding unrecrystallized ferrite in the depth area of ​​50 μm to 100 μm. The area ratio is 50% or more, and the maximum value of controlling C concentration in the hot-dip galvanized plating layer is 0.05 mass% or more to reduce the gap in the zinc-based plating layer.

Benefits of technology

The gap formation in the zinc-based plating layer of the hot stamping molded body is effectively suppressed, the spot welding properties are improved, and the strength required for the hot stamping molded body is met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116137870B_ABST
    Figure CN116137870B_ABST
Patent Text Reader

Abstract

The hot-dip galvanized steel sheet comprises a steel sheet, a boundary layer and a hot-dip galvanized coating, wherein the boundary layer is arranged on the steel sheet, and the hot-dip galvanized coating is arranged on the boundary layer. The steel sheet has a predetermined chemical composition, and in a region from the surface of the steel sheet to a depth of 25 μm from the surface of the steel sheet, the average grain size exceeds 4.0 μm, in a region from a position of 50 μm to a position of 100 μm from the surface of the steel sheet, the area ratio of unrecrystallized ferrite is 50% or more, and in the hot-dip galvanized coating, the maximum value of the C concentration is 0.05 mass% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hot-dip galvanized steel sheet.

[0002] This application claims priority based on Japanese Patent Application No. 2020-171776 filed in Japan on October 12, 2020, and the contents are incorporated herein by reference. Background Art

[0003] In recent years, from the perspective of stricter collision safety standards for automobiles and improved fuel economy, the need for higher strength of automobile components is increasing. In order to achieve higher strength of automobile components, the application of hot stamping is expanding. Hot stamping refers to a technology that performs stamping on a blank heated to a temperature above the austenite single-phase region (Ac3 point) (for example, heated to about 900°C), thereby quenching the blank by rapid cooling in the mold at the same time as forming. According to this technology, stamped products with high shape freezeability and high strength can be manufactured.

[0004] When hot stamping is applied to galvanized steel sheets, zinc components remain on the surface of the formed product after hot stamping, so the corrosion resistance is improved compared to the formed product obtained by hot stamping non-plated steel sheets. Therefore, the application of hot stamping to galvanized steel sheets is expanding.

[0005] Patent document 1 discloses a hot press-formed steel component, which has a heating process and a hot press forming process. The heating process heats the galvanized steel sheet to above the Ac3 phase transformation point. The hot press forming process performs at least two hot press forming operations after the heating process. Any hot press forming in the hot press forming process is also performed in a manner that satisfies a predetermined formula (R / t>√a·(T-b)), thereby manufacturing the hot press-formed steel component.

[0006] When hot stamping is performed on a galvanized steel sheet, welding (a phenomenon in which the copper electrode and the coating on the surface of the formed product melt and become fixed) may sometimes occur in the formed product after hot stamping during spot welding. When welding occurs during spot welding, poor welding may occur or the production line may need to be stopped to replace the copper electrode, which is not preferred. Patent Document 1 does not consider welding during spot welding.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: International Publication No. 2013 / 147228 Summary of the invention

[0010] Technical problem to be solved by the invention

[0011] The present invention has been completed in view of the above-mentioned actual situation. The object of the present invention is to provide a hot-dip galvanized steel sheet that can obtain a hot-stamped body with excellent spot weldability. In addition, the object of the present invention is to provide a hot-dip galvanized steel sheet that can obtain a hot-stamped body with the strength generally required for a hot-stamped body on the basis of having the above-mentioned characteristics.

[0012] Technical means for solving technical problems

[0013] The present inventors investigated the causes of the welding during spot welding. As a result, the present inventors realized that the welding during spot welding is greatly affected by the voids (voids) in the zinc coating of the hot stamped body (hot-dip galvanized coating after hot stamping), so the fewer the voids in the zinc coating, the more the welding during spot welding will be suppressed. The present inventors believe that due to the presence of voids in the zinc coating, the current path will be locally narrowed, overcurrent will flow there, and this place will be overheated, so that the electrode and the zinc coating will be easily welded.

[0014] In addition, although the detailed mechanism is unclear, the present inventors believe that the voids formed in the zinc coating of the hot stamped body are caused by the difference in thermal shrinkage between the steel plate and the hot-dip galvanized coating during hot stamping. Therefore, the present inventors have studied methods for reducing the difference in thermal shrinkage between the steel plate and the hot-dip galvanized coating during hot stamping. As a result, the present inventors realized that in the hot-dip galvanized steel plate, the average crystal grain size in the area from the surface of the steel plate to a depth of 25 μm from the surface of the steel plate (hereinafter sometimes recorded as the surface layer area) is set to more than 4.0 μm, the area ratio of unrecrystallized ferrite in the area from a depth of 50 μm from the surface of the steel plate to a depth of 100 μm from the surface of the steel plate is set to more than 50%, and the maximum value of the C concentration in the hot-dip galvanized coating is set to more than 0.05 mass%, thereby suppressing the generation of voids in the zinc coating of the hot stamped body.

[0015] The inventors of the present invention speculate that by setting the hot-dip galvanized steel sheet as described above, the mechanism by which the void formation in the zinc coating of the hot stamped body obtained from the hot-dip galvanized steel sheet is suppressed is as follows. By coarsening the average crystal grain size of the surface area of ​​the steel sheet to more than 4.0 μm, Fe-Zn alloying will proceed rapidly and homogeneously in the boundary layer between the steel sheet and the hot-dip galvanized coating, and the grain boundaries that are easy to become the starting point of the alloying reaction will be reduced. Therefore, the concavity and convexity of the Fe-Zn solid solution in the boundary layer will be reduced. Furthermore, it is believed that in the initial stage of heating during hot stamping, due to the presence of unrecrystallized ferrite in the region from 50 μm depth to 100 μm depth from the surface of the steel sheet, the C diffused from the steel sheet to the grain boundary portion of the boundary layer and the C in the hot-dip galvanized coating will ease the speed difference of the alloying reaction in the grain boundary portion of the above-mentioned boundary layer and the region outside it, which helps to reduce the concavity and convexity of the Fe-Zn solid solution. This can reduce the difference in thermal shrinkage between the steel sheet and the hot-dip galvanized coating during heating during hot stamping. As a result, it is estimated that the generation of voids in the galvanized coating of the hot stamped body is suppressed.

[0016] The present inventors have found that, in order to obtain the hot-dip galvanized steel sheet as described above, it is effective to maintain the steel sheet in a predetermined temperature range after hot rolling and coiling.

[0017] The gist of the present invention completed based on the above findings is as follows.

[0018] (1) A hot-dip galvanized steel sheet according to one embodiment of the present invention comprises: a steel sheet; a boundary layer disposed on the steel sheet; and a hot-dip galvanized coating layer disposed on the boundary layer;

[0019] The chemical composition of the steel plate is expressed in mass %, comprising

[0020] C: 0.18% or more, 0.50 or less,

[0021] Si: 0.10% or more, 1.50% or less,

[0022] Mn: 0.50% or more, 2.50% or less,

[0023] Al: 0.001% or more, 0.100% or less,

[0024] Ti: 0.010% or more, 0.100% or less,

[0025] S: 0.0100% or less,

[0026] P: 0.100% or less,

[0027] N: 0.0100% or less,

[0028] Nb: 0% or more, 0.05% or less,

[0029] V: 0% or more, 0.50% or less,

[0030] Cr: 0% or more, 0.50% or less,

[0031] Mo: 0% or more, 0.50% or less,

[0032] B: 0% or more, 0.0100% or less,

[0033] Ni: 0% or more and 2.00% or less, and

[0034] Total of REM, Ca, Co and Mg: 0% or more, 0.0300% or less,

[0035] The remainder is Fe and impurities;

[0036] In a region from the surface of the steel plate to a depth of 25 μm from the surface of the steel plate, an average crystal grain size exceeds 4.0 μm;

[0037] In a region from a depth of 50 μm from the surface of the steel sheet to a depth of 100 μm from the surface of the steel sheet, an area ratio of unrecrystallized ferrite is 50% or more;

[0038] In the hot-dip galvanizing layer, the maximum value of C concentration is 0.05 mass % or more.

[0039] (2) In the hot-dip galvanized steel sheet as described in (1), the chemical composition of the steel sheet may contain, in terms of mass%,

[0040] Nb: 0.02% or more, 0.05% or less,

[0041] V: 0.005% or more, 0.50% or less,

[0042] Cr: 0.10% or more, 0.50% or less,

[0043] Mo: 0.005% or more, 0.50% or less,

[0044] B: 0.0001% or more, 0.0100% or less,

[0045] Ni: 0.01% or more and 2.00% or less, and

[0046] One or more selected from the group consisting of the total amount of REM, Ca, Co and Mg: 0.0003% or more and 0.0300% or less.

[0047] (3) In the hot-dip galvanized steel sheet described in (1) or (2) above, the chemical composition of the steel sheet may contain, in mass%, C: 0.25% or more and 0.50% or less.

[0048] Effects of the Invention

[0049] According to the above aspect of the present invention, it is possible to provide a hot-dip galvanized steel sheet capable of obtaining a hot stamped product having excellent spot weldability and strength generally required for a hot stamped product. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is a schematic diagram of the GDS distribution curve of the hot-dip galvanized steel sheet according to the present embodiment. DETAILED DESCRIPTION

[0051] The hot-dip galvanized steel sheet of the present embodiment will be described in detail below. The hot-dip galvanized steel sheet of the present embodiment includes: a steel sheet; a boundary layer disposed on the steel sheet; and a hot-dip galvanized coating layer disposed on the boundary layer.

[0052] First, the steel plate constituting the hot-dip galvanized steel plate of the present embodiment will be described. Hereinafter, the reasons for limiting the chemical composition of the steel plate constituting the hot-dip galvanized steel plate of the present embodiment will be described. For numerical values ​​recorded as "above" or "below", the value is included in the numerical range. For numerical values ​​expressed as "less than" or "exceeds", the value is not included in the numerical range. All "%" for chemical composition means mass %.

[0053] The chemical composition of the steel sheet constituting the hot-dip galvanized steel sheet of the present embodiment includes, by mass%, C: 0.18% or more and 0.50% or less; Si: 0.10% or more and 1.50% or less; Mn: 0.50% or more and 2.50% or less; Al: 0.001% or more and 0.100% or less; Ti: 0.010% or more and 0.100% or less; S: 0.0100% or less; P: 0.100% or less; N: 0.0100% or less; and the remainder: Fe and impurities. The following is a description of each element.

[0054] C: 0.18% or more, 0.50 or less

[0055] C increases the strength of the hot stamped body after hot stamping. If the C content is too low, the above effect cannot be obtained. Therefore, the C content is set to 0.18% or more. Preferably, it is 0.20% or more, more than 0.20% or 0.25% or more.

[0056] On the other hand, when the C content is too high, the toughness of the hot-dip galvanized steel sheet decreases. Therefore, the C content is set to 0.50% or less. Preferably, it is 0.45% or less or 0.40% or less.

[0057] Si: 0.10% or more, 1.50% or less

[0058] Si is an element that improves the fatigue properties of hot stamped parts. In addition, Si is also an element that forms a stable oxide film on the surface of the steel sheet during recrystallization annealing in a continuous hot dip galvanizing line, thereby improving hot dip galvanizing properties, especially plating wettability. In order to obtain these effects, the Si content is set to 0.10% or more. Preferably, it is more than 0.14%, more than 0.15%, more than 0.18% or more than 0.20%.

[0059] On the other hand, when the Si content is too high, during the heating during hot stamping, the Si in the steel will diffuse and form oxides on the surface of the steel plate. The oxides formed on the surface of the steel plate will reduce the phosphate treatability. In addition, Si is also an element that increases the Ac3 point of the hot-dip galvanized steel sheet. When the Ac3 point of the hot-dip galvanized steel sheet increases, in order to fully austenitize, it is necessary to increase the heating temperature during hot stamping. As a result, the heating temperature during hot stamping sometimes exceeds the evaporation temperature of the hot-dip galvanized coating. Therefore, the Si content is set to less than 1.50%. Preferably, it is less than 1.40%, less than 1.20% or less than 1.00%.

[0060] Mn: 0.50% or more, 2.50% or less

[0061] Mn is an element that improves the hardenability of steel. In order to improve the hardenability and obtain the desired strength in the hot stamping body, the Mn content is set to 0.50% or more. Preferably, it is 1.00% or more, 1.50% or more, more than 1.50% or more, or 1.60% or more.

[0062] On the other hand, even if the Mn content is set to more than 2.50%, the effect of improving the hardenability will be saturated, and the steel will become brittle, and quenching cracks will easily occur during casting, hot rolling and cold rolling. Therefore, the Mn content is set to 2.50% or less. Preferably, it is 2.30% or less, 2.10% or less, or 2.00% or less.

[0063] Al: 0.001% or more, 0.100% or less

[0064] Al is an element that deoxidizes the molten steel and suppresses the formation of oxides that are the starting point of destruction. In addition, Al is also an element that has the effect of improving the corrosion resistance of hot stamping formed bodies. In order to obtain these effects, the Al content is set to 0.001% or more. Preferably, it is 0.005% or more.

[0065] On the other hand, when the Al content is excessive, the Ac3 point of the steel sheet will rise, and in order to fully austenitize, the heating temperature needs to be increased. As a result, the heating temperature during hot stamping will exceed the evaporation temperature of the hot-dip galvanizing coating. Therefore, the Al content is set to 0.100% or less. Preferably, it is 0.090% or less, 0.070% or less, or 0.050% or less.

[0066] Ti: 0.010% or more, 0.100% or less

[0067] Ti is an element that improves oxidation resistance after hot-dip galvanizing. In addition, Ti is also an element that combines with N in steel to form nitrides (TiN) and inhibits B from becoming nitrides (BN), thereby improving the hardenability of the steel sheet. In order to obtain these effects, the Ti content is set to 0.010% or more. Preferably, it is 0.020% or more.

[0068] On the other hand, when the Ti content is excessive, the Ac3 point will rise, and the heating temperature during hot stamping will become higher, thereby sometimes reducing productivity. In addition, when the Ti content is excessive, a large amount of Ti carbides are formed, and the amount of solid solution C is reduced, thereby reducing the strength of the hot stamped body. Furthermore, there will be a situation where the wettability of the coating is reduced, and the Ti carbides are excessively precipitated, causing the toughness of the hot stamped body to deteriorate. Therefore, the Ti content is set to 0.100% or less. Preferably, it is 0.070% or less.

[0069] S: 0.0100% or less

[0070] S is an element contained in steel as an impurity. It forms sulfides in steel, deteriorates the toughness of hot stamped parts, and reduces delayed fracture resistance. Therefore, the S content is set to 0.0100% or less. Preferably, it is 0.0050% or less.

[0071] The S content is preferably 0%. However, if the S content is excessively reduced, the S removal cost increases. Therefore, the S content may be set to 0.0001% or more.

[0072] P: 0.100% or less

[0073] P is an element contained in steel as an impurity, and is an element that segregates at grain boundaries and deteriorates the toughness and delayed fracture resistance of steel. Therefore, the P content is set to 0.100% or less. Preferably, it is set to 0.050% or less.

[0074] The P content is preferably 0%. However, if the P content is excessively reduced, the P removal cost increases. Therefore, the P content may be set to 0.001% or more.

[0075] N: 0.0100% or less

[0076] N is an impurity element, and is an element that forms coarse nitrides in steel and reduces the toughness of steel. In addition, N is also an element that is prone to produce pores during spot welding. Furthermore, when B is included, N combines with B, thereby reducing the amount of solid solution B and deteriorating the hardenability of the steel plate. Therefore, the N content is set to 0.0100% or less. Preferably, it is 0.0070% or less.

[0077] The N content is preferably 0%. However, if the N content is excessively reduced, the manufacturing cost increases, so the N content may be set to 0.0001% or more.

[0078] The remainder of the chemical composition of the steel sheet constituting the hot-dip galvanized steel sheet of the present embodiment may also be Fe and impurities. In the present embodiment, the so-called impurities mean substances mixed from the ore, waste or manufacturing environment as raw materials, and / or substances that are allowed within the range that will not adversely affect the hot stamped body manufactured using the hot-dip galvanized steel sheet of the present embodiment.

[0079] The hot-dip galvanized steel sheet of the present embodiment may contain the following elements as arbitrary elements instead of a part of Fe. When the following arbitrary elements are not contained, the content of each arbitrary element is 0%.

[0080] Nb: 0% or more, 0.05% or less,

[0081] Nb has the effect of forming carbides and refining the grains during hot stamping. By refining the grains, the toughness of the steel is improved. In order to reliably obtain this effect, it is preferred that the Nb content be set to 0.02% or more. However, when the Nb content is too high, the above effect may be saturated and the hardenability of the steel may be reduced. Therefore, the Nb content is set to 0.05% or less.

[0082] V: 0% or more, 0.50% or less

[0083] V is an element that improves the strength of steel by forming fine carbonitrides in the steel. In order to reliably obtain this effect, the V content is preferably set to 0.005% or more.

[0084] On the other hand, when the V content exceeds 0.50%, the toughness of the steel decreases during spot welding, and cracks are easily generated. Therefore, the V content is set to 0.50% or less.

[0085] Cr: 0% or more, 0.50% or less

[0086] Cr is an element that improves the hardenability of steel. In order to reliably obtain this effect, it is preferable that the Cr content be 0.10% or more.

[0087] On the other hand, when the Cr content is too high, Cr carbides are formed in the steel, and the Cr carbides are difficult to dissolve during heating for hot stamping, which deteriorates the hardenability. Therefore, the Cr content is set to 0.50% or less.

[0088] Mo: 0% or more, 0.50% or less

[0089] Mo is an element that improves the hardenability of steel. In order to reliably obtain this effect, it is preferable that the Mo content be 0.005% or more.

[0090] However, if the Mo content is too high, the above effect is saturated. Therefore, the Mo content is set to 0.50% or less.

[0091] B: 0% or more, 0.0100% or less

[0092] B is an element that improves the hardenability of steel. In order to reliably obtain this effect, it is preferable that the B content be 0.0001% or more.

[0093] On the other hand, even if the B content is too high, the effect of improving the hardenability is saturated. Therefore, the B content is made 0.0100% or less.

[0094] Ni: 0% or more, 2.00% or less

[0095] Ni is an element that has the effects of improving the toughness of steel, suppressing embrittlement due to liquid Zn during heating for hot stamping, and improving the hardenability of steel. In order to reliably obtain these effects, the Ni content is preferably set to 0.01% or more.

[0096] On the other hand, even if the Ni content is too high, the above-mentioned effect is saturated. Therefore, the Ni content is made 2.00% or less.

[0097] Total of REM, Ca, Co and Mg: 0% or more, 0.0300% or less

[0098] REM, Ca, Co, and Mg are elements that control sulfides and oxides to a preferred shape and suppress the formation of coarse inclusions, thereby suppressing the occurrence of cracks during spot welding. In order to reliably obtain this effect, it is preferred that the total content of REM, Ca, Co, and Mg be 0.0003% or more. In addition, in order to reliably obtain the above effect, any one of REM, Ca, Co, and Mg may be contained as long as its content is 0.0003% or more.

[0099] On the other hand, if the total content of REM, Ca, Co and Mg is too high, inclusions are excessively generated, and cracks are easily generated during spot welding. Therefore, the total content of REM, Ca, Co and Mg is set to 0.0300% or less.

[0100] The chemical composition of the steel sheet can be measured by general analytical methods. For example, it can be measured by ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). In addition, C and S can be measured by combustion-infrared absorption method, and N can be measured by inert gas melting-heat conduction method. The chemical composition analysis can be performed after removing the boundary layer and hot-dip galvanized coating disposed on the surface of the hot-dip galvanized steel sheet by mechanical grinding.

[0101] The steel sheet constituting the hot-dip galvanized steel sheet of the present embodiment has the above-mentioned chemical composition, and in the region from the surface of the steel sheet to a depth of 25 μm from the surface of the steel sheet (surface region), the average crystal grain size exceeds 4.0 μm, and in the region from a depth of 50 μm from the surface of the steel sheet to a depth of 100 μm from the surface of the steel sheet, the area ratio of unrecrystallized ferrite is 50% or more. The following is a detailed description of each provision.

[0102] Surface area: average crystal grain size exceeds 4.0 μm

[0103] In the present embodiment, the so-called surface region refers to the region from the surface of the steel plate to a depth of 25 μm from the surface of the steel plate. By setting the average crystal grain size in the surface region to more than 4.0 μm, the Fe-Zn alloying between the steel plate and the hot-dip galvanized coating can be carried out rapidly and homogeneously during the heating during hot stamping. In addition, Zn diffuses in the grain boundaries, which easily become the starting point of the Fe-Zn alloying reaction. Therefore, by making the grains in the surface region coarse, the grain boundaries are reduced, thereby reducing the starting point of the Fe-Zn alloying reaction. Through these effects, the concavo-convexity of the Fe-Zn solid solution can be reduced, the thermal shrinkage difference between the steel plate and the hot-dip galvanized coating can be reduced during hot stamping, and the formation of voids can be suppressed in the zinc coating of the hot stamped body. As a result, the desired spot weldability can be obtained in the hot stamped body. Therefore, in the surface region of the steel plate, the average crystal grain size is set to more than 4.0 μm. Preferably, the average crystal grain size in the surface layer region of the steel sheet is set to 4.3 μm or more, 4.5 μm or more, or 4.8 μm or more.

[0104] The upper limit of the average crystal grain size in the surface layer region of the steel sheet does not need to be particularly limited, but may be 14.0 μm or less. From the viewpoint of further improving the spot weldability, it is preferably 10.0 μm or less.

[0105] Method for measuring the average crystal grain size in the surface layer region

[0106] The average grain size of the surface layer region is measured by EBSP-OIM (Electron Back Scatter Diffraction Pattern-Orientation Image Microscopy) method. The EBSP-OIM method is performed using a scanning electron microscope combined with an EBSP analyzer and OIM Analysis (registered trademark) manufactured by AMETEK.

[0107] In the plate thickness section parallel to the rolling direction, from the surface of the steel plate to the area 25 μm deep from the surface of the steel plate, the analysis was performed in at least 5 fields of view at a magnification of 1200 times in an area of ​​40 μm × 30 μm. The place where the angle difference between adjacent measurement points is 5° or more is defined as the grain boundary, and the equivalent circle diameter of the grain is calculated and regarded as the crystal grain size. The average crystal grain size in the surface area is obtained by calculating the average value of the crystal grain size of the obtained crystal grains.

[0108] In addition, the steel sheet, the boundary layer, and the hot-dip galvanizing layer are identified by the method described later, and the above-mentioned measurement may be performed on the region identified as the steel sheet.

[0109] Hereinafter, a method of specifying the steel sheet, the boundary layer, and the hot-dip galvanizing layer will be described.

[0110] At any position of the hot-dip galvanized steel sheet, from the surface to 50 μm in the depth direction (plate thickness direction), the concentrations (mass %) of Fe, Zn and C were measured by GDS (glow discharge luminescence analysis). When the hot-dip galvanized steel sheet of this embodiment is measured by GDS, the following can be obtained: Figure 1 In the present embodiment, the depth range where the Fe concentration is 85 mass % or more is defined as the steel plate, and the depth range where the Zn concentration is 90 mass % or more is defined as the hot-dip galvanized coating. In addition, the depth range between the steel plate and the hot-dip galvanized coating is defined as the boundary layer.

[0111] Region from 50 μm deep to 100 μm deep from the surface of the steel sheet: The area ratio of unrecrystallized ferrite is 50% or more

[0112] By setting the area ratio of unrecrystallized ferrite in the region of 50 μm depth to 100 μm depth from the surface of the steel plate to 50% or more, C will easily diffuse to the grain boundary near the interface between the steel plate and the hot-dip galvanized coating in the initial stage of heating during hot stamping. As a result, the Fe-Zn alloying reaction rate in the grain boundary near the above-mentioned interface can be reduced, and the speed difference of the Fe-Zn alloying reaction in the grain boundary near the above-mentioned interface and the region outside it can be reduced. Through their actions, the unevenness of the Fe-Zn solid solution can be reduced, the thermal shrinkage difference between the steel plate and the hot-dip galvanized coating can be reduced during hot stamping, and the formation of voids in the galvanized coating of the hot stamped body can be suppressed. As a result, the desired spot weldability can be obtained in the hot stamped body. Therefore, the area ratio of unrecrystallized ferrite in the above-mentioned region is set to 50% or more. Preferably, it is 60% or more.

[0113] The area ratio of non-recrystallized ferrite in the above region is not particularly limited, but may be 80% or less. From the viewpoint of further improving spot weldability, it is preferably 70% or less.

[0114] In the present embodiment, the remaining structure other than the unrecrystallized ferrite in the region of 50 μm depth to 100 μm depth from the surface of the steel plate may include, in terms of area%, ferrite: 0 to 50%, bainite and martensite: 0 to 50%, pearlite: 0 to 50%, and retained austenite: 0 to 5%. In addition, the ferrite mentioned here does not include unrecrystallized ferrite.

[0115] Method for determining the area ratio of unrecrystallized ferrite

[0116] From the hot-dip galvanized steel sheet, a test piece was collected with the plate thickness section parallel to the rolling direction of the steel sheet as the observation surface. After the observation surface of the test piece was polished, nital etching was performed. In the area of ​​the observation surface from 50 μm to 100 μm from the surface of the steel sheet, in one or more fields of view, a total of 4.0×10 -8 m 2 The above areas were analyzed for crystal orientation using the electron backscatter diffraction method (EBSD) based on FE-SEM. Based on the obtained crystal orientation diagram of bcc iron, the boundaries with orientation differences of 5.0° or more were regarded as grain boundaries. Furthermore, the crystal orientation variation (GOS: Grain Orientation Spread) within the grains was calculated, and the grains with GOS of 1.0° or more were regarded as unrecrystallized ferrite, and their area ratio was obtained.

[0117] For analysis of crystal orientation, OIM Data Collection and OIM Data Analysis manufactured by TSL can be used.

[0118] The metal structure inside the steel plate is not particularly limited as long as the desired strength and spot weldability can be obtained after hot stamping, but it can also be composed of the total of unrecrystallized ferrite and ferrite: 0-100%, bainite and martensite: 0-100%, pearlite: 0-80% and retained austenite: 0-5%, in terms of area%. In addition, in the present embodiment, the so-called inside of the steel plate refers to a position at a depth of 1 / 4 of the plate thickness from the surface of the steel plate (an area from a depth of 1 / 8 of the plate thickness from the surface of the steel plate to a depth of 3 / 8 of the plate thickness from the surface). The metal structure at this position represents a representative metal structure of the steel plate. The metal structure of the steel plate can be measured by the following method.

[0119] Method for determining the area ratio of ferrite and pearlite

[0120] The area ratio of ferrite and pearlite is determined by the following method. A test piece with a thickness section parallel to the rolling direction of the steel plate as the observation surface is collected from the hot-dip galvanized steel plate. The observation surface of the test piece is finished into a mirror surface, and the observation surface is polished for 8 minutes at room temperature with colloidal silica that does not contain an alkaline solution to remove the strain introduced into the observation surface. At any position in the rolling direction of the steel plate in the observation surface, the area with a length of 50 μm and a depth of 1 / 8 of the thickness from the surface of the steel plate to a depth of 3 / 8 of the thickness from the surface of the steel plate is measured by electron backscatter diffraction at a measurement interval of 0.1 μm in a manner that allows analysis of a depth of 1 / 4 of the thickness from the surface of the steel plate to obtain crystal orientation information. For the measurement, a device consisting of a thermal field emission scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSP detector (DVC5 detector manufactured by TSL) is used. At this time, the vacuum degree in the device is set to 9.6×10 -5 Pa or less, the acceleration voltage was 15 kV, the irradiation current level was 13, and the irradiation level of the electron beam was 62. Furthermore, a reflected electron image was photographed in the same field of view.

[0121] First, the crystal grains formed by lamellar precipitation of ferrite and cementite are determined based on the reflected electron image, and the area ratio of the crystal grains is calculated, thereby obtaining the area ratio of pearlite. Then, for the crystal grains other than the crystal grains determined as pearlite, the "Grain Average Misorientation" function installed in the software "OIM Analysis (registered trademark)" attached to the EBSP analysis device is used for the obtained crystal orientation information, and the area with a grain average orientation difference of 1.0° or less is determined as ferrite. By obtaining the area ratio of the area determined as ferrite, the area ratio of ferrite is obtained.

[0122] Determination method of area ratio of retained austenite

[0123] The area ratio of retained austenite is measured by electron backscatter diffraction (EBSD). In the analysis based on EBSD, a test piece collected at the same collection position as the area ratio of the ferrite and pearlite is used. In a manner that can analyze the depth of 1 / 4 of the thickness from the surface of the steel plate, the area with a length of 50 μm and a depth of 1 / 8 of the thickness from the surface of the steel plate to a depth of 3 / 8 of the thickness from the surface of the steel plate is measured. After grinding the observation surface of the test piece with silicon carbide paper of #600 to 1500, the observation surface is finished into a mirror surface using a liquid obtained by dispersing diamond powder with a particle size of 1 to 6 μm in a diluent such as alcohol or pure water. Then, the strain of the observation surface is fully removed by electrolytic grinding. In addition, in electrolytic grinding, in order to remove the mechanical grinding strain of the observation surface, the minimum grinding thickness can be 20 μm, and the maximum grinding thickness can be 50 μm. Considering the collapse of the end, the thickness to be ground is preferably 30 μm or less.

[0124] Regarding the measurement under EBSD, the acceleration voltage is set to 15-25 kV, and the measurement is performed at intervals of at least 0.25 μm or less, and the crystal orientation information of each measurement point in the range of 150 μm or more in the plate thickness direction and 250 μm or more in the rolling direction is obtained. The crystal structure obtained is determined as retained austenite by using the "Phase Map" function in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device. The area ratio of retained austenite is obtained by calculating the proportion of measurement points determined to be retained austenite. Here, the more measurement points, the better, so it is better when the measurement interval is narrower and the measurement range is larger. However, when the measurement interval is less than 0.01 μm, the adjacent points will interfere with the expansion width of the electron beam. Therefore, the measurement interval is set to 0.01 μm or more. In addition, the maximum measurement range can also be set to 200 μm in the plate thickness direction and 400 μm in the plate width direction. For the measurement, a device consisting of a thermal field emission scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSP detector (DVC5 detector manufactured by TSL) was used. At this time, the vacuum degree in the device was set to 9.6×10 -5 Pa or less, the irradiation current level is 13, and the electron beam irradiation level is 62.

[0125] Method for determining the area ratio of bainite and martensite

[0126] The total area ratio of bainite and martensite is defined as a value obtained by subtracting the total area ratio of ferrite and pearlite and the area ratio of retained austenite measured by the above-mentioned method from 100%.

[0127] The hot-dip galvanized steel sheet of the present embodiment includes: the above-mentioned steel sheet; a boundary layer disposed on the steel sheet; and a hot-dip galvanized coating layer disposed on the boundary layer. The boundary layer and the hot-dip galvanized coating layer will be described below.

[0128] Boundary layer

[0129] In the present embodiment, the so-called boundary layer refers to a layer existing between the above-mentioned steel plate and the hot-dip galvanized coating described later. In the present embodiment, the depth range where the Fe concentration is 85% by mass or more is defined as the steel plate, and the depth range where the Zn concentration is 90% by mass or more is defined as the hot-dip galvanized coating. Thus, the depth range where the Fe concentration is less than 85% by mass and the Zn concentration is less than 90% by mass can be defined as the boundary layer.

[0130] Hot dip galvanizing coating

[0131] In the present embodiment, the so-called hot-dip galvanized coating refers to a layer with a Zn concentration of 90% by mass or more. When the maximum value of the C concentration in the hot-dip galvanized coating is less than 0.05% by mass, the evaporation of zinc in the hot-dip galvanized coating during heating during hot stamping cannot be suppressed, and a large number of voids will be formed in the hot stamped body. As a result, the desired spot weldability cannot be obtained in the hot stamped body. Therefore, the maximum value of the C concentration in the hot-dip galvanized coating is set to 0.05% by mass or more. Preferably, it is 0.10% by mass or more or 0.15% by mass or more.

[0132] The upper limit of the maximum value of the C concentration in the hot-dip galvanizing layer is not particularly limited, but may be 0.50 mass % or less.

[0133] In addition, the hot-dip galvanized layer may contain 0.01 mass % to 1.00 mass % of Al as an element other than Zn, and may contain 10 mass % or less of Fe as the remainder.

[0134] Method for determining the maximum carbon concentration in hot-dip galvanized coatings

[0135] At any 5 locations of the hot-dip galvanized steel sheet, the concentrations (mass %) of Fe, Zn and C are measured from the surface to 50 μm in the depth direction (plate thickness direction) by GDS (glow discharge luminescence analysis). At each measurement position, the depth range where the Fe concentration is 85 mass % or more is defined as the steel sheet, the depth range where the Zn concentration is 90 mass % or more is defined as the hot-dip galvanized coating, and the depth range between the steel sheet and the hot-dip galvanized coating is defined as the boundary layer. Next, the maximum value of the C concentration (mass %) in the depth range defined as the hot-dip galvanized coating is determined. The maximum value of the C concentration in the hot-dip galvanized coating is obtained by calculating the average value of the maximum values ​​of the C concentration in the depth range defined as the hot-dip galvanized coating at each measurement position.

[0136] Plate thickness

[0137] The plate thickness of the hot-dip galvanized steel plate of the present embodiment is not particularly limited, but is preferably 0.5 to 3.5 mm from the viewpoint of reducing the weight of the vehicle body.

[0138] Next, a preferred method for producing the hot-dip galvanized steel sheet according to the present embodiment will be described.

[0139] First, the billet having the above chemical composition is heated to 1200°C or higher, and hot rolled after being held in a temperature range of 1200°C or higher for 20 minutes or more. The final rolling is completed in a temperature range of 810°C or higher, and coiling is performed in a temperature range of 550°C or higher and 750°C or lower. Then, the billet is held in a temperature range of 700°C or higher for 15 minutes or more and less than 120 minutes.

[0140] In a preferred method for manufacturing the hot-dip galvanized steel sheet of the present embodiment, after hot rolling and coiling, the steel sheet is kept in a temperature range of 700°C or higher for 15 minutes or more and less than 120 minutes. This allows the grains in the surface region of the steel sheet to be coarsened, and a desired amount of non-recrystallized ferrite can be obtained in a region at a depth of 50 μm to 100 μm from the surface of the steel sheet.

[0141] In addition, during the holding in the temperature range above 700°C, the temperature of the steel sheet may be varied or kept constant. The upper limit of the holding temperature may be set to be below the Ac1 point from the viewpoint of suppressing the generation of hard low-temperature transformation phases such as martensite and bainite and the viewpoint of refining the average crystal grain size in the surface layer region. The Ac1 point can be represented by the following formula (1).

[0142] Ac1(℃)=723-10.7×Mn+29.1×Si-16.9×Ni+16.9×Cr…(1)

[0143] Here, the symbol of the element in formula (1) represents the content of the element in mass %. When the element is not contained, 0 is substituted.

[0144] After being kept in a temperature range of 700°C or higher for 15 minutes or more and less than 120 minutes, cold rolling is performed as needed, and hot-dip galvanizing is performed. Pickling may also be performed between hot rolling and cold rolling. Cold rolling is performed at a normal cumulative reduction rate, for example, cold rolling at a cumulative reduction rate of 30 to 90%.

[0145] Hot dip galvanizing can be performed using a continuous hot dip galvanizing line. The amount of hot dip galvanizing coating is not particularly limited and can be a general amount. For example, the coating amount per single side can be set to 5 to 150 g / m 2 .

[0146] When the hot-dip galvanized layer is alloyed to form an alloyed hot-dip galvanized layer, the high Zn concentration Γ phase in the coating layer that plays a sacrificial corrosion protection role disappears, and the corrosion resistance decreases. In electrogalvanizing, an additive element is required to delay alloying, which increases the manufacturing cost and is therefore not desirable.

[0147] The hot-dip galvanized steel sheet according to the present embodiment can be manufactured by the above method.

[0148] When producing a hot stamped body, it is preferable to hot stamp the hot-dip galvanized steel sheet of the present embodiment under the following conditions.

[0149] First, it is preferred that the hot-dip galvanized steel sheet of the present embodiment is heated so that the heating temperature becomes the higher temperature of "Ac3 point and 800°C" to 950°C. In addition, it is preferred that the heating time (the time from when the hot-dip galvanized steel sheet is placed in the heating furnace, maintained at the heating temperature, to when the hot-dip galvanized steel sheet is taken out of the heating furnace (the time from when the hot-dip galvanized steel sheet is placed in the heating furnace to when the hot-dip galvanized steel sheet is taken out of the heating furnace)) is set to 60 to 600 seconds. In addition, the Ac3 point is represented by the following formula (2).

[0150] Ac3(℃)=910-203×C 0.5 -30×Mn+44.7×Si+400×Ti…(2)

[0151] The symbol of the element in formula (2) represents the content of the element in mass %.

[0152] By setting the heating temperature to a higher temperature of "Ac3 point and 800°C" and the heating time to more than 60 seconds, austenitization can be fully performed, and as a result, a hot stamping formed body with desired strength can be obtained. By setting the heating temperature to 950°C or less and the heating time to 600 seconds or less, excessive alloying can be suppressed. The average heating rate during heating can be set to 0.1 to 200°C / s. The average heating rate mentioned here is the value obtained by dividing the temperature difference between the surface temperature of the steel plate at the start of heating and the heating temperature by the time difference from the start of heating to the time when the heating temperature is reached. While maintaining the temperature range of the higher temperature of "Ac3 point and 800°C" to 950°C, the temperature of the steel plate can be changed or kept constant.

[0153] Examples of the heating method before hot stamping include heating with an electric furnace, a gas furnace, or the like, flame heating, electric heating, high-frequency heating, and induction heating.

[0154] After the above-mentioned heating and holding, hot stamping is performed. After hot stamping, for example, it is preferable to cool at an average cooling rate of 20 to 500°C / s to a temperature range of 250°C or less.

[0155] By the above method, a hot stamped part made of the hot-dip galvanized steel sheet of the present embodiment can be obtained. With respect to the hot stamped part, the formation of voids in the zinc coating (hot-dip galvanized coating after hot stamping) is suppressed, so the spot weldability is excellent and the hot stamped part has the strength generally required.

[0156] [Example]

[0157] Next, the embodiments of the present invention will be described, but the conditions in the embodiments are a conditional example adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this conditional example. As long as it does not deviate from the gist of the present invention and achieves the purpose of the present invention, the present invention can adopt various conditions.

[0158] The billet produced by casting the molten steel having the chemical composition shown in Table 1A and Table 1B was heated to 1200°C or higher, maintained for more than 20 minutes, hot rolled so that the final rolling completion temperature was 810°C or higher, and coiled in a temperature range of 550°C to 750°C. Next, it was heated to the temperature shown in Table 2A and Table 2B and maintained at the temperature. Then, it was cold rolled to obtain a steel sheet.

[0159] The cumulative reduction rate during cold rolling was set to 30-90%. The obtained steel sheets were subjected to a continuous hot-dip galvanizing line to form a hot-dip galvanized layer, thereby obtaining the hot-dip galvanized steel sheets shown in Table 2A and Table 2B. The amount of hot-dip galvanized layer adhered was set to 5-150 g / m per single side. 2 .

[0160] For the obtained hot-dip galvanized steel sheet, the average crystal grain size in the region from the surface of the steel sheet to a depth of 25 μm from the surface of the steel sheet (surface region), the metal structure in the region from a depth of 50 μm from the surface of the steel sheet to a depth of 100 μm from the surface of the steel sheet, and the maximum value of the C concentration of the hot-dip galvanized coating were measured by the above method. In addition, in Table 2A and Table 2B, "average crystal grain size" is the average crystal grain size in the region from the surface of the steel sheet to a depth of 25 μm from the surface of the steel sheet (surface region), and "unrecrystallized α" is the area ratio of unrecrystallized ferrite in the region from a depth of 50 μm from the surface of the steel sheet to a depth of 100 μm from the surface of the steel sheet.

[0161] The hot-dip galvanized steel sheets obtained were subjected to the conditions shown in Tables 2A and 2B to obtain the hot stamped bodies shown in Tables 2A and 2B. In addition, the average heating rate in the heating before hot stamping was set to 0.1 to 200°C / s, and after hot stamping, the average cooling rate was 20 to 500°C / s until the temperature range was below 250°C.

[0162] The underlined parts in the table indicate that the conditions are outside the scope of the present invention, deviate from the preferred production conditions, or the characteristic values ​​are not preferred.

[0163] With respect to the obtained hot stamped formed body, the cross-sectional area ratio of voids in the zinc-based plating layer constituting the hot stamped formed body was measured by the following method.

[0164] First, a test piece with a cross section (plate thickness cross section) perpendicular to the surface as the observation surface is cut from any position more than 50 mm away from the end face of the hot stamped body (if it is not possible to collect from this position, it is a position avoiding the end). The size of the test piece is set to a size that can be observed along the rolling direction of about 10 mm.

[0165] Next, the observation surface was polished, photographed with a SEM (scanning electron microscope) at a magnification of 300 times, and the cross-sectional area ratio of the voids was calculated by binary image processing. For the calculation of the cross-sectional area ratio of the voids, the built-in software of the digital microscope VHX-5000 manufactured by Keyence was used to perform void discrimination based on brightness and automatic void area measurement.

[0166] Regarding the steel plate and zinc-based coating that constitute the hot stamped body, SEM-EDS (Energy Dispersive X-ray Spectroscopy) was used to perform line analysis along the thickness direction and quantitative analysis of Fe concentration, thereby making a distinction. In this embodiment, SEM (NB5000 manufactured by Hitachi High-technologies), EDS (XFlash(r)6│30 manufactured by Bruker AXS), and EDS analysis software (ESPRIT1.9 manufactured by Bruker AXS) were used. When performing SEM observation, the area that is closest to the center of the plate thickness in the plate thickness direction and has an Fe content of more than 80% by mass excluding the measurement noise is judged as a steel plate, and the area other than it is judged as a zinc-based coating.

[0167] The mechanical properties (tensile strength and spot weldability) of the hot stamped parts were evaluated by the following methods.

[0168] Tensile Strength

[0169] Regarding the tensile strength of the hot stamped body, a No. 5 test piece described in JIS Z 2241: 2011 was made from any position of the hot stamped body and obtained according to the test method described in JIS Z 2241: 2011. When the tensile strength is 1500 to 2500 MPa, it has the strength generally required for hot stamped bodies, so it is judged to be qualified. In addition, when the tensile strength is less than 1500 MPa, the strength is poor, so when the tensile strength exceeds 2500 MPa, the strength is too high, and the toughness and ductility are poor, so it is judged to be unqualified.

[0170] Spot weldability

[0171] Two test pieces of 100 mm×30 mm were collected from the hot stamped body except for the region within 10 mm from the end surface, and the two test pieces were overlapped and spot welding was performed while changing the current under the following conditions.

[0172] Pressure: 400kgf

[0173] Power-on time: 15 cycles

[0174] Hold time: 9 cycles

[0175] Electrode tip shape: DR type, front end - Radius of curvature R40mm

[0176] The current at which the spot diameter is 4√t (t is the thickness of the test piece) is recorded as I0, and the current that causes welding (welding current I s ).

[0177] In addition, for the obtained welding current I s The spot weldability was evaluated using the following criteria: I0 (kA): the current at which the spot diameter is 4√t (t is the thickness of the test piece), continuous spot current I a (kA): I0×1.4. The examples evaluated as “good” and “acceptable” were excellent in spot weldability and were judged as acceptable, while the examples evaluated as “unacceptable” were poor in spot weldability and were judged as unacceptable.

[0178] Good: I s >I a ×1.15

[0179] Fair: I a ×1.10<I s ≤I a ×1.15

[0180] Bad: I s ≤Ia ×1.10

Table 1A

[0181]

[0182]

Table 1B

[0183]

[0184]

Table 2A

[0185]

[0186]

Table 2B

[0187]

[0188] It can be seen from Table 2A and Table 2B that the hot-dip galvanized steel sheets of the present invention have a tensile strength of 1500-2500 MPa, and the cross-sectional area ratio of voids is reduced to less than 15.0%, and as a result, a hot stamped body with excellent spot weldability is obtained. In particular, in the hot stamped bodies of Manufacturing No. 1 to 25, the cross-sectional area ratio of voids is reduced to less than 13.0%, and the spot weldability is even better.

[0189] In addition, for the hot-dip galvanized steel sheets of the present invention examples in Tables 2A and 2B, the remaining structure other than the unrecrystallized ferrite in the region from 50 μm depth to 100 μm depth from the surface of the steel sheet includes, by area%, ferrite: 0 to 50%, bainite and martensite: 0 to 50%, pearlite: 0 to 50%, and retained austenite: 0 to 5%. In addition, the metal structure inside the steel sheet includes, by area%, the total of unrecrystallized ferrite and ferrite: 0 to 100%, bainite and martensite: 0 to 100%, pearlite: 0 to 80%, and retained austenite: 0 to 5%.

[0190] On the other hand, regarding the hot-dip galvanized steel sheets of the comparative examples in Table 2B, it was found that the obtained hot stamped bodies had tensile strengths outside the range of 1500 to 2500 MPa and / or the cross-sectional area ratio of voids exceeded 15.0% and had poor spot weldability.

[0191] Industrial Availability

[0192] According to the above aspect of the present invention, it is possible to provide a hot-dip galvanized steel sheet, which can provide a hot stamped product having excellent spot weldability and strength generally required for a hot stamped product.

Claims

1. A hot-dip galvanized steel sheet, characterized in that: include: Steel plate, a boundary layer disposed on the steel plate, and A hot-dip galvanizing coating layer disposed on the boundary layer; The chemical composition of the steel plate is expressed in mass %, comprising C: 0.18% or more, 0.50 or less, Si: 0.10% or more, 1.50% or less, Mn: 0.50% or more, 2.50% or less, Al: 0.001% or more, 0.100% or less, Ti: 0.010% or more, 0.100% or less, S: 0.0100% or less, P: 0.100% or less, N: 0.0100% or less, Nb: 0% or more, 0.05% or less, V: 0% or more, 0.50% or less, Cr: 0% or more, 0.50% or less, Mo: 0% or more, 0.50% or less, B: 0% or more, 0.0100% or less, Ni: 0% or more and 2.00% or less, and Total of REM, Ca, Co and Mg: 0% or more, 0.0300% or less, The remainder is Fe and impurities; In a region from the surface of the steel sheet to a depth of 25 μm from the surface of the steel sheet, an average crystal grain size exceeds 4.0 μm and is not more than 14.0 μm; In a region from a depth of 50 μm from the surface of the steel sheet to a depth of 100 μm from the surface of the steel sheet, an area ratio of unrecrystallized ferrite is 50% or more; In the hot-dip galvanizing layer, the maximum value of C concentration is 0.05 mass % or more.

2. The hot-dip galvanized steel sheet according to claim 1, characterized in that: The chemical composition of the steel sheet contains one or more selected from the group consisting of the following elements in mass %: Nb: 0.02% or more, 0.05% or less, V: 0.005% or more, 0.50% or less, Cr: 0.10% or more, 0.50% or less, Mo: 0.005% or more, 0.50% or less, B: 0.0001% or more, 0.0100% or less, Ni: 0.01% or more and 2.00% or less, and Total of REM, Ca, Co and Mg: 0.0003% or more and 0.0300% or less.

3. The hot-dip galvanized steel sheet according to claim 1 or 2, characterized in that: The chemical composition of the steel plate, expressed in mass%, contains C: 0.25% or more and 0.50% or less.

Citation Information

Patent Citations

  • Game program, method, and information processing device

    JP2020171776A

  • Manufacturing method for hot press-molded steel member, and hot press-molded steel member

    WO2013147228A1

  • Zinc hot-dipped steel sheet

    CN110959048A